Chicana/o identity in a changing U.S. society quién soy? quiénes somos? - Hurtado, Aída (Mexican American experience., 2004)
Examines the development of the Chicano communities in the United States, identifies the relationship between individual ethnic groups, discusses the influence on American culture, and covers issues such as immigration and intermarriage.